Rouge : a novel - Awad, Mona (Marysue Rucci Books, an imprint of Simon & Schuster, Inc., 2023)
"For as long as she can remember, Belle has been insidiously obsessed with her skin and skincare videos. When her estranged mother Noelle mysteriously dies, Belle finds herself back in Southern California, dealing with her mother's considerable debts and grappling with lingering questions about her death. The stakes escalate when a strange woman in red appears at the funeral, offering a tantalizing clue about her mother's demise, followed by a cryptic video about a transformative spa experience. With the help of a pair of red shoes, Belle is lured into the barbed embrace of La Maison de Méduse, the same lavish, culty spa to which her mother was devoted. There, Belle discovers the frightening secret behind her (and her mother's) obsession with the mirror--and the great shimmering depths (and demons) that lurk on the other side of the glass. Snow White meets Eyes Wide Shut in this surreal descent into the dark side of beauty, envy, grief, and the complicated love between mothers and daughters. With black humor and seductive horror, Rouge explores the cult-like nature of the beauty industry--as well as the danger of internalizing its pitiless gaze. Brimming with California sunshine and blood-red rose petals, Rouge holds up a warped mirror to our relationship with mortality, our collective fixation with the surface, and the wondrous, deep longing that might lie beneath"--